Nonhermetic Encapsulation Materials for MEMS-Based Movable Microelectrodes for Long-Term Implantation in the Brain - Jackson, Nathan (2009)
In this paper, we have fabricated and tested several composite materials with a mesh matrix, which are used as encapsulation materials for a novel implantable movable-microelectrode microelectromechanical-system (MEMS) device. Since movable microelectrodes extend off the edge of the MEMS chip and penetrate the brain, a hermetically sealed encapsulation was not feasible. An encapsulation material is needed to prevent cerebral-spinal-fluid entry that could cause failure of the MEMS device and, at the same time, allow for penetration by the microelectrodes. Testing of potential encapsulation materials included penetration-force measurements, gross-leak testing, maximum-pressure testing, and biocompatibility testing. Penetration-force tests showed that untreated mesh matrices and silicone-gel-mesh composites required the least amount of force to penetrate for both nylon 6,6 and polypropylene meshes. The silicone-gel-, poly(dimethylsiloxane)-, polyimide-, and fluoroacrylate-mesh composites with the nylon-mesh matrix were all able to withstand pressures above the normal intracranial pressures. Fourier-transform infrared-spectroscopy analysis and visual inspection of the implanted devices encapsulated by the silicone-gel-mesh composite showed that there was no fluid or debris entry at two and four weeks postimplantation. We conclude that a composite of nylon and silicone-gel meshes will meet the needs of the new generation of implantable devices that require nonhermetic encapsulation.